Trade, tasks, and training: The effect of offshoring on individual skill upgrading - Jan Hogrefe; Jens Wrona (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2014)
We offer a theoretical explanation and empirical evidence for a positive link between increased offshoring and individual skill upgrading. Skill upgrading takes the form of on-thejob training, complementing the existing literature, which mainly focuses on the retraining of workers after a direct job displacement through offshoring. To establish a link between offshoring and on-the-job training, we introduce an individual skill upgrading margin into a variant of the Grossman and Rossi-Hansberg (2008) model of offshoring. By scaling up worker's wages, offshoring in our model creates previously unexploited skill upgrading possibilities and, thus, leads to more on-the-job training. Using data from German manufacturing, we establish a causal link between the growth in industry-level offshoring and an increased on-the-job training propensity at the individual level.
Keywords: F10; F16; F61; 330; Offshoring; Tasks; Skill upgrading; On-the-job training